ANALYSIS OF MATHEMATICAL CONNECTION ABILITY WHEN SOLVED PROBLEM IN 7th GRADE SMPN 9 BURU - Rusmin Madia; Nining Halimombo (IAIN Ambon, 2022)
This research was conducted with the aim of knowing the ability of students' mathematical connections to the solution of contextual problems of social arithmetic materials class VIID SMPN 9 Buru. This type of research is qualitative research prioritizing process deepening over results, researchers as the main instrument and supporting instruments (tests and interviews), put forward field research that requires researchers to be in the context of research. This research began from March 15 to 14, 2018 SMPN 9 Buru. Data analysis techniques are reduction, presentation, and conclusion drawing. The results showed that students' mathematical connection ability in solving contextual problems in social arithmetic materials in class VIID SMPN 9 Buru, namely students meet indicators of mathematical connection ability according to NCTM (National Council of Teachers of Mathematics), namely; Recognizing and utilizing the relationships between ideas in mathematics, students are able to complete test questions by writing down what is known, asked answered, writing the right mathematical model and correct answers; Understanding ideas in mathematics are interconnected and underlying with each other to produce a coherent wholeness, students are able to answer problems using mathematical notations such as subtraction, addition and multiplication, and calculate properly and correctly; And knowing and using mathematics in contexts outside mathematics, students are able to associate mathematical concepts with everyday life, such as economics related to the problem of profit and loss in trading.Key words: Mathematical Connection Ability, Contextual, Social Arithmetic